Phenotypic and genetic characterization of daptomycin non-susceptible Staphylococcus aureus strains selected by adaptive laboratory evolution - Yanlei Xu; Yanghua Xiao; Huilin Zhao; Bingjie Wang; Jingyi Yu; Yongpeng Shang; Ying Zhou; Xiaocui Wu; Yinjuan Guo; Fangyou Yu (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundDaptomycin non-susceptible Staphylococcus aureus (DNS) strains pose a serious clinical threat, yet their characteristics remain poorly understood.MethodsDNS derivatives were generated by exposing S. aureus strains to subinhibitory concentrations of daptomycin. Competition experiment and growth kinetics experiment were used to observe the growth of bacteria. Galleria mellonella larvae and mouse skin abscess models were used to observe the virulence of bacteria. Transmission electron microscopy (TEM), cytochrome C experiment and biofilm formation experiment were used to observe the drug resistance phenotype. And homologous recombination was used to study the role of mutations.ResultsPhenotypic profiling of DNS strains revealed impaired growth, increased cell wall thickness, enhanced biofilm formation, reduced negative surface charge, and attenuated virulence compared to their wild-type strains. Whole genome sequencing identified mutations in mprF, cls2, and saeR in DNS strains. Allelic replacement experiments validated the roles of MprF L341F and Cls2 F60S substitutions in augmenting daptomycin non-susceptibility in Newman. Deletion of saeR in the NewmanMprFL341F strain and complementation of saeR in the Newman-DNS strain did not directly alter daptomycin susceptibility. However, the deletion of saeR was found to enhance competitive fitness under daptomycin pressure.ConclusionThis work validates adaptive laboratory evolution (ALE) for modeling clinical DNS strains and uncovers contributions of mprF, cls2, and saeR mutations to the adaptation and resistance mechanisms of S. aureus against daptomycin. These findings enrich our understanding of how S. aureus acquired resistance to daptomycin, thus paving the way for the development of more effective treatment strategies and offering potential molecular markers for resistance surveillance.